Reintegrating Poso: A Comparative Study of Islam and Christianity in Sayo and Pamona Villages - Ruagadi, Henry Anderson (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2024)
This study aims to analyze Post-Conflict Social Reintegration in Poso. Post-conflict social reintegration in Poso needs to be carried out to realize lasting peace in Poso Regency and prevent the recurrence of conflicts. The study was conducted using a qualitative approach. Data collection was carried out by interviewing 24 Muslim and Christian informants in Sayo and Pamona Villages. The results of the study found: 1. Social Reintegration of Islam and Christianity in Sayo Village and Pamona Village after the Poso Conflict, namely building trust between Muslims and Christians by Cultivating tolerance, mutual respect, appreciation, living and loving; increasing the role of religious leaders in providing soothing spiritual watering; instilling an attitude of loyalty in citizens; instilling an attitude of mutual trust through family education. Common identity, joint activities, and pro-reintegration policymaking also strengthened it. In realizing reintegration, Muslims and Christians have a strong desire to realize lasting peace. Finally, there are three values of Sintuwu Maroso as the most effective Local Wisdom in integrating Islamic and Christian societies after the Poso Conflict, namely: Tuwu Metubunaka, Mombepatuwu and Mombepomawo. These three values are infused and applied by Muslims and Christians in Sayo and Pamona Villages to blend in with each other, coexist, stay away from prejudice, accept each other and respect each other.